The Impact of Mindfulness Education on Elementary School Students (Indian Journal of Forensic Medicine & Toxicology, 2020)
The current research aims at evaluating the reading for the fourth grade of primary school in the light of the habits of mind and followed the researcher descriptive approach to suitability the current research procedures to achieve the research objective, the researcher prepared a list that included the criteria of habits of mind based on this researcher prepared a questionnaire (6) standards and (141) paragraphs after verifying the authenticity of the tool from its presentation to a group of arbitrators the stability of the analysis using Holistic equation (0.83) The tool consists of (128) paragraphs distributed in six areas The researcher has developed three alternatives (valid), (invalid), (need to be modified), and the researcher used the appropriate statistical means for their research. The data obtained from the analysis process are: Holistic equation, centimeter weight, square cay, and weighted mean.
Keywords: Evaluation, Arabic Reading Book, Habits of Mind